A Molecular and Biochemical Study for Cholesteryl Ester Transfer Protein (CETP) Taq1B in Iraqi Patients with Hyperlipidemia (Baghdad Science Journal, 2019)
Cholesteryl ester transfer protein gene contains some single nucleotide polymorphisms, which have been associated with serum high-density lipoprotein concentration and other lipoproteins. This study is done for determining of cholesteryl ester transfer protein polymorphism and evaluate its effect on serum lipid profile concentrations in some hyperlipidemic patients compared with healthy subjects in Salah Al-din governorate-Iraq. Blood samples were taken from (90) patients suffering from hyperlipidemia, and (70) samples that were apparently healthy controls. Serum lipid concentrations were measured by enzymatic assays. The polymorphism was genotyped using polymerase chain reaction restriction fragment length polymorphism analysis. The results showed that there was a significant decrease (P<0.05) in the frequency B2 allele, and B1B2, B2B2 genotype, and a significant increase (P<0.05) in the frequency B1 allele, and B1B1 genotype between patients and controls groups. There was a non-significant decrease in the levels of high density lipoproteins, total cholesterol, low density lipoproteins, and very low density lipoproteins levels, and non-significant increase in levels of triglycerides in individuals with the B1B1 genotype than in the B1B2 and B2B2 genotype. However, high density lipoproteins showed a significant decrease (P<0.001) between individuals with the B1B1 genotype and B2B2 genotype. Also, there was a non-significant difference in the levels of high density lipoproteins, total cholesterol, low density lipoproteins, and very low density lipoproteins levels, in individuals with the B1B2 genotype when compared with that of the B2B2 genotype.